Connecting the World: The Quality of Teachihg and Learning Process Reflected from Students’ Creativity on Micro Teaching Subject - Rohmat Rohmat (TARBIYA: Journal of Education in Muslim Society, 2016)
Abstract This research is intended to see students’ creativity level on microteaching subject of Islamic Education Major Program Faculty of Tarbiyah and Teachers’ Training of IAIN Surakarta in 2015. This research was descriptive. The 6th semester students of Islamic Education Major Program were the participants of this research in micro teaching class. Interview and document were used as the instruments with the microteaching lecturer as the informant. Interactive analysis was applied for data analysis. The results show that the quality of students’ creativity in developing lesson plan as follows: (1)The lesson plan (RPP) developed before teaching improves learning quality (2)the interactive activities mentioned in the lesson plan (RPP) contain the learning strategies and facilities encouraging teaching and learning process (3)learning goals were achieved during the teaching and learning process. (4)the learning techniques is associated with the component of instructional system (5)teaching media was used to conduct conducive learning situation (6)some contents emphasized in the lesson plan (RPP) were suitable with the instructions existed in course book and curriculum (7)some specific activities done by the students in the learning process are their ways to master the materials they taught (8)The learning focus is emphasized on PAIKEM (Active, Innovative, Creative, Effective, and Fun Learning) and on evaluation to check the result, process, and comprehensible instruction. Abstrak Penelitian ini bertujuan untuk mengetahui tingkat kreatifitas siswa pada pembelajaran micro teaching pada jurusan Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruan IAIN Surakarta tahun 2015. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Populasi dalam penelitian ini adalah mahasiswa mata kuliah micro teaching semester VI. Instrumen penelitian yang digunakan adalah wawancara dan dokumen yang mana dosen mata kuliah tersebut menjadi informan penelitian. Hasil penelitian menunjukkan bahwa kreatifitas para siswa pada matakuliah micro teaching sebagai berikut: 1)Pembuatan RPP dapat meningkatkan kualitas pembelajaran. 2)kegiatan interaktif yang tertera dalam RPP berisi langkah-langkah strategi pembelajaran interaktif dan fasilitas yang mendukung proses belajar mengajar; 3)tujuan didapatkan dalam proses belajar mengajar. 4)teknik pembelajaran dilakukan dan disesuaikan dengan kandungan dari sistem instruksional. 5)penggunaan media ajar kondusif. 6)penekanan yang dipaparkan dalam RPP disesuaikan dnegan instruksi yang ada dalam buku dan kurikulum. 7)hal-hal spesifik yang dilakukan para mahasiswa dalam proses pembelajaran merupakan strategi untuk menguasai materi yang akan diajarkan. 8)fokus dalam pembelajaran ditekankan pada PAIKEM (Pembelajaran Aktif, Inovatif, Kreatif, Efektif, dan Menyenangkan) dan evaluasi untuk mengetahui hasil, proses, dan instruksi yang komprehensif. How to Cite : Rohmat. (2016) Connecting the World: The Quality of Teachihg and Learning Process Reflected from Students’ Creativity on Micro Teaching Subject. TARBIYA: Journal of Education in Muslim Society, 3(2), 227-241. doi:10.15408/tjems.v3i2.4062. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i2.4062